Rancangan Model Bisnis Pudidud (Puding Endud) Berbasis BMC - Prayitno, Rizqi Apriliani; Zahra, Cut; Najwa, Chika Naili Ilmatun; Ramadhani, Levina; Azhara, Dhea Fahmi; Ardiastati, Arfika; Ramadhani, Artika; Setiawati, Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Pudding is a popular dessert among various age groups. "Pudidud (Puding Endud)" is a healthy snack product featuring flavor innovation and unique packaging. This study aims to design the Pudidud business model using the Business Model Canvas (BMC) approach. A descriptive qualitative method with a case study was used on the Pudidud business in Bandung. Data were collected through observation, documentation, and in-depth interviews with the business owner and two staff members in production and marketing. The results show that Pudidud has high market potential by targeting teenagers and young adults with healthy lifestyles and strong social media engagement. Its strengths lie in using natural ingredients and eco-friendly packaging. This article presents a 9-block BMC structure and business development strategies based on a SWOT analysis.